Tradisi Kungkuman Tugu Soeharto Dalam Perspektif Psikologi - Qurnia Fitriyatinur (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the shift in the value of the Kungkuman Tugu Suharto tradition in a psychological perspective. This research is elaborative with a qualitative approach. The sample used in this study were five subjects. Data collection techniques in this research by means of interviews. The results of this study indicate that the kungkum ritual at Tugu Soeharto currently has a transformation of social change with different meanings and goals. The kungkum ritual which was originally always associated with the means of seeking the